Four‐dimensional Monte Carlo simulations demonstrating how the extent of intensity‐modulation impacts motion effects in proton therapy lung treatments. Issue 12 (14th November 2013) - Dowdell, Stephen; Grassberger, Clemens; Paganetti, Harald
Abstract : Purpose: : To compare motion effects in intensity modulated proton therapy (IMPT) lung treatments with different levels of intensity modulation. Methods: : Spot scanning IMPT treatment plans were generated for ten lung cancer patients for 2.5Gy(RBE) and 12Gy(RBE) fractions and two distinct energy‐dependent spot sizes (σ ∼8–17 mm and ∼2–4 mm). IMPT plans were generated with the target homogeneity of each individual field restricted to <20% (IMPT20% ). These plans were compared to full IMPT (IMPTfull ), which had no restriction on the single field homogeneity. 4D Monte Carlo simulations were performed upon the patient 4DCT geometry, including deformable image registration and incorporating the detailed timing structure of the proton delivery system. Motion effects were quantified via comparison of the results of the 4D simulations (4D‐IMPT20%, 4D‐IMPTfull ) with those of a 3D Monte Carlo simulation (3D‐IMPT20%, 3D‐IMPTfull ) upon the planning CT using the equivalent uniform dose (EUD), V95 and D1 ‐D99 . The effects in normal lung were quantified using mean lung dose (MLD) and V90% . Results: : For 2.5Gy(RBE), the mean EUD for the large spot size is 99.9% ± 2.8% for 4D‐IMPT20% compared to 100.1% ± 2.9% for 4D‐IMPTfull . The corresponding values are 88.6% ± 8.7% (4D‐IMPT20% ) and 91.0% ± 9.3% (4D‐IMPTfull ) for the smaller spot size. The EUD value is higher in 69.7% of the considered deliveries for 4D‐IMPTfull . The V95 is also higher in 74.7% of the plans for 4D‐IMPTfull, implying that IMPTfull plans experience less underdose compared to IMPT20% . However, the target dose homogeneity is improved in the majority (67.8%) of plans for 4D‐IMPT20% . The higher EUD and V95 suggests that the degraded homogeneity in IMPTfull is actually due to the introduction of hot spots in the target volume, perhaps resulting from the sharper in‐target dose gradients. The greatest variations between the IMPT20% and IMPTfull deliveries are observed for patients with the largest motion amplitudes. These patients would likely be treated using gating or another motion mitigation technique, which was not the focus of this study. Conclusions: : For the treatment parameters considered in this study, the differences between IMPTfull and IMPT20% are only likely to be clinically significant for patients with large (>20 mm) motion amplitudes.